Cloud Computing : Assessing the Risks. - Carstensen, Jared (IT Governance Publishing, 2012)
Cloud Computing: Assessing the risks answers these questions and many more. Using jargon-free language and relevant examples, analogies and diagrams, it is an up-to-date, clear and comprehensive guide the security, governance, risk, and compliance elements of Cloud Computing.